Lung CT image of a confirmed case of the 2019 novel coronavirus (2019-nCoV) infected pneumonia (with differential diagnosis of the SRAS) - Li LI; Mei-Ji REN; Yan-Yan ZHANG; Wen-Qiao LI; Hai-Yan ZHAO; Lian-Chun LIANG; Rong-Hua JIN; Hai-Ping XIANG; Zhong-Jie HU; Hong-Jun LI (Yixue xinzhi zazhi)
Without the.